Review of Smart Grid Technology and the Nigerian Electricity Act: Addressing Power Sector Challenges Through Policy and Innovation - Patrick, D. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Energy policy plays a crucial role in shaping the energy landscape of any region. The reform of the Nigerian Electricity Act in 2023 marked a significant milestone for the Nigerian electricity market. It established a legal foundation aimed at addressing the nation’s perennial energy crisis by enabling the adoption of modern sustainable technologies and initiatives into the Nigerian power industry. Poor policy implementation, inadequate generation, and unplanned downtime due to faults on the defunct transmission and distribution networks have stifled the growth of power delivery in Nigeria, emphasizing the need for more intelligent and sustainable power infrastructure. This paper presents a comprehensive review of the challenges in Nigeria’s power sector and explores how emerging technologies can provide effective solution at every node of the power chain. It draws insights from global case studies and outlines a strategic roadmap and timeline for planning and implementing smart grid and sustainable initiatives in Nigeria. Additionally, it highlights critical considerations necessary to promoting long-term sustainability within Nigeria’s power industry.